2017
DOI: 10.1111/bju.13860
|View full text |Cite
|
Sign up to set email alerts
|

Cytoreductive nephrectomy in the era of targeted therapies: a review

Abstract: In the pre-targeted therapy era, palliative cytoreductive nephrectomy combined with cytokine immunotherapy was the standard treatment protocol for the management of metastatic renal cell carcinoma. The introduction of targeted therapies has improved response rates, median survival and overall prognosis when compared to immunotherapy. The role of cytoreductive nephrectomy in providing an independent survival advantage when used alongside immunotherapy has been demonstrated by two randomised controlled trials. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 85 publications
(68 reference statements)
1
15
0
1
Order By: Relevance
“…It is implicit in our high‐risk patient population with mRCC that the causes of death within the 90‐day window were likely attributed to either surgery‐accounted adverse events or rapid progression of metastatic disease. As previous studies have reported, not all patients are likely to benefit from surgery, and patient selection is essential when considering CN for mRCC . The high 90‐day mortality rate suggests that there might be still room for improvement in CN patient selection in the real‐world practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is implicit in our high‐risk patient population with mRCC that the causes of death within the 90‐day window were likely attributed to either surgery‐accounted adverse events or rapid progression of metastatic disease. As previous studies have reported, not all patients are likely to benefit from surgery, and patient selection is essential when considering CN for mRCC . The high 90‐day mortality rate suggests that there might be still room for improvement in CN patient selection in the real‐world practice.…”
Section: Discussionmentioning
confidence: 99%
“…surgery, and patient selection is essential when considering CN for mRCC. 3,4,6 The high 90-day mortality rate suggests that there might be still room for improvement in CN patient selection in the real-world practice. The difference in baseline patient characteristics between our two hospital volume groups also suggests that high-volume groups might be more selective in the patient selection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The decreased tumor burden that occurred with the disappearance of the primary tumor lesion provided better prognostic outcomes with systemic TT. However, good performance status and a primary tumor accounting for >75% of the overall tumor burden without any metastatic lesions in the central nervous system and liver did not yield a better prognostic outcome for every mRCC patient after cytoreductive nephrectomy, which resulted in a low rate of nephrectomy in the targeted era [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the presence of metastases confers worse survival, the role of surgery in patients with advanced RCC has evolved and in select patients, plays an important role in modern management algorithms, even in the era of targeted therapy [23][24][25]. Proponents of cytoreductive surgery in RCC have cited such benefits as reduction in the burden of disease, removal of potential new metastatic sources, spontaneous tumor regression, reversal of host immune dysfunction, and symptom palliation to support the practice [26][27][28][29][30]. In addition,…”
mentioning
confidence: 99%